2017
DOI: 10.1002/art.39962
|View full text |Cite
|
Sign up to set email alerts
|

Anifrolumab, an Anti–Interferon‐α Receptor Monoclonal Antibody, in Moderate‐to‐Severe Systemic Lupus Erythematosus

Abstract: ObjectiveTo assess the efficacy and safety of anifrolumab, a type I interferon (IFN) receptor antagonist, in a phase IIb, randomized, double‐blind, placebo‐controlled study of adults with moderate‐to‐severe systemic lupus erythematosus (SLE).MethodsPatients (n = 305) were randomized to receive intravenous anifrolumab (300 mg or 1,000 mg) or placebo, in addition to standard therapy, every 4 weeks for 48 weeks. Randomization was stratified by SLE Disease Activity Index 2000 score (<10 or ≥10), oral corticosteroi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
623
2
18

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 703 publications
(664 citation statements)
references
References 30 publications
21
623
2
18
Order By: Relevance
“…A secondary analysis of the SRI-6 response was undertaken to examine whether the SRI-6 primary end point may have been confounded by imbalances in corticosteroid taper. In this end point, adapted from a recently published trial result,14 response was defined as meeting the week 52 SRI-6 criteria while also having an oral corticosteroid dose from week 40 through week 52 that was lower than the dose on day 1. With this analysis, 23.3% of blisibimod-treated subjects met the end point vs 14.3% of the control arm (P=0.056, figure 2F).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A secondary analysis of the SRI-6 response was undertaken to examine whether the SRI-6 primary end point may have been confounded by imbalances in corticosteroid taper. In this end point, adapted from a recently published trial result,14 response was defined as meeting the week 52 SRI-6 criteria while also having an oral corticosteroid dose from week 40 through week 52 that was lower than the dose on day 1. With this analysis, 23.3% of blisibimod-treated subjects met the end point vs 14.3% of the control arm (P=0.056, figure 2F).…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, when steroid reduction is included in the end point, analogous to the phase II SLE trial with anifrolumab,14 lower responder rates were observed and greater treatment effect with blisibimod. The secondary analyses of the effects of blisibimod on corticosteroid taper suggest that background corticosteroid use may have confounded the primary efficacy end point, since many of the control subjects received corticosteroid doses that were higher than baseline throughout the trial, averaging 3–5 mg/day higher than the blisibimod group, in which the mean dose was below baseline from week 12 onwards.…”
Section: Discussionmentioning
confidence: 99%
“…Measuring the IFN signature in patients with SLE might in the future be used in clinical decision-making 8. The necessity to quantify gene expression and the lack of a uniformly accepted gene set or scoring system hamper its implementation in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Anifrolumab, a monoclonal antibody against IFNAR, the receptor for type I IFN, showed clinical efficacy in a phase IIb clinical trial in SLE, particularly in those patients with an IFN signature 8. The detection of the IFN signature may therefore soon be used to guide treatment decisions in SLE and possibly other autoimmune diseases.…”
mentioning
confidence: 99%
“…In this latter trial, the absolute percentage difference in clinical response between patients treated with the highest dose of sifalimumab and those treated with placebo was 14% [80], similar to the absolute percentage differences observed in the successful trial with belimumab or tabalumab. Of note, however, were results from the phase-IIb trial of the anti-IFNα receptor mAb, anifrolumab, in which the absolute percentage difference in clinical response between patients treated with the optimal dose of anifrolumab and those treated with placebo being 26% [81]. Although comparisons of response rates across different trials are notoriously unreliable and must be taken with a large grain of salt, the strikingly greater response rate in the trial that targeted the IFNα receptor rather than IFNα itself raises the plausibility of im-proved results in BAFF-centric trials that target BAFF receptors rather than BAFF itself.…”
Section: ) Targeting Of Baff Receptors Rather Than Of Baffmentioning
confidence: 99%